The influence of work experience on entrepreneurial intentions and opportunity recognition: A focus on postgraduate students in South Africa - Volkersz, Roderick (My University, 2019)
The objective of this study was to examine the relationships between the human capital variable work experience with opportunity identification and entrepreneurial intention. The study focused on postgraduate students with work experience and sought to establish the existence of links between their work experience and their opportunity recognition process, as well as their work experience and their entrepreneurial intention. The study examined previous literature, which highlighted that students with previous work experience had higher levels of entrepreneurial intention, compared with students without previous work experience. Thus, the study set out to examine the relationship between these constructs, including opportunity recognition in the process. The study was a cross-sectional, quantitative study, which followed a positivist paradigm approach. Primary data was collected from postgraduate students through a self-administered questionnaire. Data analysis included exploratory factor analysis, reliability and validity testing, linear regression and correlational analysis. The study found that work experience was not a significant predictor of opportunity recognition or entrepreneurial intention. The study also highlighted that there were negative relationships between work experience and opportunity recognition, as well as work experience and entrepreneurial intention. The study’s findings are important in that they could help the youth, in particular students, who would like to pursue their own entrepreneurial ventures to understand the knowledge and experience required to successfully develop a new business. Key words: work experience; opportunity recognition; entrepreneurial intention; postgraduate students; South Africa.
A research report submitted to the faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management specialising in Entrepreneurship and New Venture Creation Johannesburg, 2019
Keywords: Entrepreneurship--South Africa; Business enterprises--South Africa